PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA APARAT PEMERINTAH DAERAH. STUDI KASUS PADA KANTOR BADAN KEUANGAN DAN ASET DAERAH KABUPATEN MANGGARAI) - Clara Margilia Reinamah (JAKA - Jurnal Jurusan Akuntasi, 2022)
The purposes of this study are: 1) The Effect of Participation in Budgeting to the Performance of Local Government personnel in Manggarai Regency; 2) The Effect of Organizational Commitment to the Performance of Local Government personnel in Manggarai Regency; 3) The Effect of Participation in Budgeting and Organizational Commitment to the Performance of Local Government personnel in Manggarai Regency. The type of this research is causative research. The type of data used in this study are quantitative and qualitative data. While the data sources used are primary and secondary. The variables used in this study are the dependent variable and the independent variable. Data collection techniques were carried out by documenting and distributing questionnaires to structural officials and several staff who were directly related and also participated in the budgeting process at the Office of the Regional Finance and Assets Agency of Manggarai Regency. The analytical method used is Multiple Linear Regression. The results of the study prove that 1) Participation in budgeting has no significant effect on the performance of local government officials. 2) Organizational commitment has a significant effect on the performance of local government officials. 3) budgetary participation and organizational commitment have a significant effect on the performance of local government officials